School engagement and motivation: a conceptual discussion - Sandoval-Muñoz, María José (2018)
The present research work aims at gaining understanding of what it is referred as “motivation” and “engagement” in the context of educational  processes considering points of consensus and debate in the specialized literature. The objective was examining how far the definitions that have been proposed by authors from English-speaking contexts are compatible or have been represented in writings from Iberoamerican context attempting to clarify how are these two constructs related to each other. A review was performed focusing on manuscripts that discussed advances in these subjects. The main conclusions from this revision highlight the similarity of some definitions for both concepts. It is shown that both concepts are being treated as equivalent to each other, enabling potential conceptual confusions. The need for further debating about the relationship between both kinds of processes aiming at achieving higher clarity regarding the differences between the concepts to help future research and interventions is proposed.